2014
DOI: 10.1007/s12035-014-9003-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Provides Insights on Paraquat-Induced Parkinson-Like Symptoms in Drosophila melanogaster

Abstract: Paraquat (PQ) exposure causes degeneration of the dopaminergic neurons in an exposed organism while altered metabolism has a role in various neurodegenerative disorders. Therefore, the study presented here was conceived to depict the role of altered metabolism in PQ-induced Parkinson-like symptoms and to explore Drosophila as a potential model organism for such studies. Metabolic profile was generated in control and in flies that were fed PQ (5, 10, and 20 mM) in the diet for 12 and 24 h concurrent with assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 91 publications
0
39
1
Order By: Relevance
“…In some of the earlier studies, acute exposure to PQ led to increased activity of SOD [17,35], whereas, others have reported reduced activity of SOD at higher dose [37,38]. In our study, flies exposed to multiple-dose of PQ showed a markedly decreased activity of both Cu/Zn-SOD and mitochondrial Mn-SOD in contrast to the acute exposure.…”
contrasting
confidence: 44%
“…In some of the earlier studies, acute exposure to PQ led to increased activity of SOD [17,35], whereas, others have reported reduced activity of SOD at higher dose [37,38]. In our study, flies exposed to multiple-dose of PQ showed a markedly decreased activity of both Cu/Zn-SOD and mitochondrial Mn-SOD in contrast to the acute exposure.…”
contrasting
confidence: 44%
“…Here we examined the effect of PACAP in a widely used sporadic PD model induced by PQ exposure in Drosophila (34,37,39,87). Since the fly orthologue of PACAP has not yet been identified with confidence (41), we used the amino acid sequence of PACAP-38, which is identical in all mammals, and because PACAP could not cross the intestinal barrier and remain intact, we directly applied the neuropeptide to the exposed VNC of decapitated Drosophila before PQ exposure, using a previously established procedure (39).…”
Section: Discussionmentioning
confidence: 99%
“…For Gal80 ts experiments, 5-day-old female flies were shifted to 29°C. For paraquat experiments, 5 day-old-female flies were shifted to 2 mM paraquat in a sucrose- (5%) and agar-containing (1.3%) medium ( Shukla et al, 2014 ). For Gene-Switch experiments, 5-day-old flies were transferred to standard or paraquat media and were supplemented with 200 μM RU486.…”
Section: Methodsmentioning
confidence: 99%